The Role of Vitamin D and Physical Activity in Endometriosis: Implications for Pain Relief, Physical Function and Reproductive Health- A Literature-Based Review - Głowacka, Aleksandra; Kurek, Aleksandra; Domińczak, Dominika; Ivanchuk, Sofiia; Górecki, Patryk; Kaminskaya, Anhelina; Savchak, Tetiana; Feretycki, Hubert; Salama, Aladdin; Abdulla, Shafea (Quality in Sport, 2026)
Purpose of research. The aim of this study was to evaluate the roles of vitamin D and physical activity in the management of endometriosis, with particular emphasis on their effects on pain reduction, physical function, and reproductive health in affected women. Research materials and methods. A literature-based review was conducted using major scientific databases, including PubMed, Scopus, and Web of Science. The analysis included original studies, randomized controlled trials, systematic reviews, and meta-analyses focusing on vitamin D status, supplementation, and physical activity interventions in women with endometriosis. Basic results. Vitamin D exhibits immunomodulatory, anti-inflammatory, antiproliferative, and anti-angiogenic properties mediated through the vitamin D receptor (VDR), which is widely expressed in reproductive tissues. Lower serum levels of 25-hydroxyvitamin D may be associated with increased risk and severity of endometriosis; however, clinical evidence regarding pain reduction remains inconsistent. Physical activity, including aerobic exercise and mind–body interventions such as yoga, has been shown to reduce pain, improve quality of life, and positively influence psychological well-being through anti-inflammatory and neuroendocrine mechanisms. Emerging evidence suggests that optimizing vitamin D levels, combined with regular physical activity, may produce synergistic effects, particularly in improving physical performance, reducing inflammation, and supporting bone health. Conclusions. Vitamin D and physical activity may serve as safe and effective complementary strategies in the management of endometriosis. Their integration into a personalized, multidisciplinary approach may improve patient outcomes; however, further high-quality studies are required to establish standardized clinical guidelines.